2022
DOI: 10.1161/atvbaha.122.317518
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Arterial Elastocalcinosis: Differential Roles of the Conserved Glutamic Acid and Serine Residues of Matrix Gla Protein

Abstract: Background: Mutations in matrix Gla protein gene (MGP ) lead to Keutel syndrome, a rare disease hallmarked by ectopic calcification of cartilage and vascular tissues. Although MGP (matrix Gla protein) acts as a strong inhibitor of arterial elastic lamina calcification (elastocalcinosis), its mode of action is unknown. Two sets of conserved residues undergoing posttranslational modifications—4 glutamic acid residues, which are γ-carboxylated by gamma-glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Thus, in this population that is already at risk for vascular calcification, the effect of warfarin is quantitatively very large and likely to lead to substantial morbidity. The greater effect of warfarin in ESRD is consistent with recent studies in which genetic inactivation of MGP did not result in vascular calcification unless the mice were fed a high phosphate diet, 18 presumably mimicking the hyperphosphatemia that is common in ESRD.…”
Section: Figuresupporting
confidence: 86%
“…Thus, in this population that is already at risk for vascular calcification, the effect of warfarin is quantitatively very large and likely to lead to substantial morbidity. The greater effect of warfarin in ESRD is consistent with recent studies in which genetic inactivation of MGP did not result in vascular calcification unless the mice were fed a high phosphate diet, 18 presumably mimicking the hyperphosphatemia that is common in ESRD.…”
Section: Figuresupporting
confidence: 86%
“…173 Both, the conserved glutamic acid residues and N-terminal conserved serine residues contribute to its antimineralization function. 174,175 Vitamin K is essential for the activation and mineral inhibitory effects of MGP, and individuals with CKD often exhibit vitamin K deficiency, 176 likely contributing to the decreased active MGP in these patients and subsequent vascular calcification. The elevated thromboembolic risk in patients with CKD requires anticoagulation.…”
Section: Mgp and Vitamin K Supplementationmentioning
confidence: 99%
“… 173 Both, the conserved glutamic acid residues and N-terminal conserved serine residues contribute to its antimineralization function. 174 , 175 …”
Section: Therapeutic Modulation Of Mineral Formation Growth and Compo...mentioning
confidence: 99%
“…In addition, the expression of MGP in chondrocytes is regulated by extracellular inorganic phosphorus, which may represent a feedback regulatory mechanism to inhibit inappropriate calcification in cartilage ( 84 ). Of note, ectopic expression of MGP in human osteosarcoma (OS) cells significantly increased cancer cell metastasis to the lung in patients with OS, which may lead to poor prognosis ( 88 ). In general, MGP maintains bone health by affecting cartilage mineralization, osteoblast function and osteoclast activity.…”
Section: Vkdps Are Essential In Biomineralizationmentioning
confidence: 99%
“…However, a recent study suggested something different. Parashar et al ( 88 ) constructed MGP mutant mice and found that the serine residues at the MGP N-terminus and glutamate at the C-terminus had a synergistic effect to inhibit vascular tissue calcification; however, the serine residues had a more critical role. In addition, a study used immunohistochemistry to confirm that cMGP and pMGP have anti-calcification effects in veins ( 89 ).…”
Section: Vkdps Are Essential In Biomineralizationmentioning
confidence: 99%